Method for manufacturing fibrous carbon nanostructures and surface-modified fibrous carbon nanostructures
Patent Information
- Application Number
- KR1020227020615
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-15
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2040-12-15
Smart Images

Figure 112022063160307-PCT00001
Abstract
Description
Technology Field
[0001] The present invention relates to a fibrous carbon nanostructure and a method for manufacturing a surface-modified fibrous carbon nanostructure. Background Technology
[0002] In recent years, fibrous carbon nanostructures such as carbon nanotubes (hereinafter referred to as “CNT”) have attracted attention as materials with excellent conductivity, thermal conductivity, and mechanical properties.
[0003] However, fibrous carbon nanostructures such as CNTs tend to form bundle structures due to van der Waals forces, making them difficult to disperse in solvents; consequently, there were cases where properties such as conductivity could not be fully exhibited.
[0004] Accordingly, active development is underway for technologies to obtain surface-modified fibrous carbon nanostructures with improved dispersibility by performing various surface modification treatments on fibrous carbon nanostructures such as CNTs.
[0005] For example, Patent Document 1 proposes a technique for improving the dispersibility of a CNT in a solvent by performing a liquid-phase oxidation treatment as a surface modification treatment on a CNT having an intensity ratio (G / D ratio) of 50 or more in Raman spectroscopic analysis. Prior art literature
[0006] International Publication No. 2018 / 043487 The problem to be solved
[0007] However, as a result of the inventor's review, the fibrous carbon nanostructures used in the surface modification treatment of the prior art had room for improvement in dispersibility after the surface modification treatment.
[0008] Accordingly, the present invention aims to provide a fibrous carbon nanostructure with excellent dispersibility after surface modification treatment.
[0009] In addition, the present invention aims to provide a surface-modified fibrous carbon nanostructure with excellent dispersibility. means of solving the problem
[0010] The inventors have conducted thorough investigations to achieve the above objective. The inventors have discovered that a fibrous carbon nanostructure, in which the amount of localized electrons obtained by measuring electron spin resonance at a temperature of 10K is greater than a predetermined value, exhibits excellent dispersibility after surface modification treatment, thereby completing the present invention.
[0011] That is, the present invention aims to advantageously solve the above problem, wherein the fibrous carbon nanostructure of the present invention has a localized electron quantity of 1.0 × 10⁻⁶ obtained by electron spin resonance measurement at a temperature of 10K. 17 It is characterized by having a quantity of at least one g. As such, the fibrous carbon nanostructure, in which the localized electron quantity obtained by electron spin resonance measurement at a temperature of 10K is greater than a predetermined value, has excellent dispersibility after surface modification treatment.
[0012] Meanwhile, in the present invention, the amount of localized electrons obtained by measuring the electron spin resonance of a fibrous carbon nanostructure at a temperature of 10K can be measured by the method described in the examples of this specification.
[0013] Here, the fibrous carbon nanostructure of the present invention preferably has a ratio of the G band peak intensity to the D band peak intensity in a Raman spectrum (G / D ratio) of 0.5 or more and 5.0 or less. By keeping the G / D ratio within the above predetermined range, the dispersibility of the fibrous carbon nanostructure after surface modification treatment can be further enhanced. Accordingly, the fibrous carbon nanostructure can exhibit particularly excellent properties (e.g., conductivity, thermal conductivity, and strength, etc. Hereinafter, may be simply referred to as "properties") after surface modification treatment.
[0014] Meanwhile, in the present invention, the ratio of the G band peak intensity to the D band peak intensity in the Raman spectrum (G / D ratio) can be measured by the method described in the examples of this specification.
[0015] In addition, the fibrous carbon nanostructure of the present invention has a localized electron quantity of 1.0 × 10 19 It is preferable that the local electron quantity is less than the specified value. If the local electron quantity is less than the above-mentioned value, when surface modification treatment is performed on the fibrous carbon nanostructure, the loss of the fibrous carbon nanostructure after surface modification treatment is suppressed, and the surface-modified fibrous carbon nanostructure can be obtained efficiently.
[0016] In addition, it is preferable that the fibrous carbon nanostructure of the present invention exhibits an upwardly convex shape in the t-plot obtained from the adsorption isotherm. If the t-plot obtained from the adsorption isotherm exhibits an upwardly convex shape, the fibrous carbon nanostructure can exhibit particularly excellent properties when dispersibility is enhanced by surface modification treatment.
[0017] In addition, the fibrous carbon nanostructure of the present invention preferably comprises carbon nanotubes. If the fibrous carbon nanostructure comprises carbon nanotubes, excellent properties can be exhibited when dispersibility is enhanced by surface modification treatment.
[0018] In addition, the fibrous carbon nanostructure of the present invention preferably comprises single-layer carbon nanotubes as carbon nanotubes. If the fibrous carbon nanostructure comprises single-layer carbon nanotubes as carbon nanotubes, it can exhibit particularly excellent properties when dispersibility is enhanced by surface modification treatment.
[0019] Furthermore, the present invention aims to advantageously solve the above problem. The method for manufacturing a surface-modified fibrous carbon nanostructure according to the present invention is characterized by including a process of obtaining a surface-modified fibrous carbon nanostructure by performing a surface modification treatment on any one of the fibrous carbon nanostructures described above. According to the method for manufacturing a surface-modified fibrous carbon nanostructure according to the present invention, a surface-modified fibrous carbon nanostructure with excellent dispersibility can be manufactured.
[0020] In addition, in the method for manufacturing a surface-modified fibrous carbon nanostructure according to the present invention, the surface modification treatment is preferably a wet oxidation treatment. By using a wet oxidation treatment as the surface modification treatment, the dispersibility of the surface-modified fibrous carbon nanostructure manufactured can be further enhanced. Effects of the invention
[0021] According to the present invention, a fibrous carbon nanostructure with excellent dispersibility after surface modification treatment can be provided.
[0022] In addition, according to the present invention, a surface-modified fibrous carbon nanostructure with excellent dispersibility can be provided. Specific details for implementing the invention
[0023] Hereinafter, embodiments of the present invention will be described in detail.
[0024] (fibrous carbon nanostructures)
[0025] The fibrous carbon nanostructure of the present invention is characterized by having a localized electron quantity obtained by measuring electron spin resonance at a temperature of 10K that is greater than or equal to a predetermined value. Since the localized electron quantity of the fibrous carbon nanostructure of the present invention is greater than or equal to the predetermined value, the dispersibility after surface modification treatment is excellent. Therefore, the surface-modified fibrous carbon nanostructure obtained by performing surface modification treatment on the fibrous carbon nanostructure of the present invention can exhibit excellent dispersibility in a solvent such as water. Accordingly, when various molded articles (e.g., films such as antistatic films or conductive films) are formed using a dispersion of the obtained surface-modified fibrous carbon nanostructure, the amount of agglomeration in said molded article can be reduced. Accordingly, the molded article made of the formed surface-modified fibrous carbon nanostructure has excellent properties such as conductivity, thermal conductivity, and strength. That is, the surface-modified fibrous carbon nanostructure obtained by performing surface modification treatment on the fibrous carbon nanostructure of the present invention can be said to have excellent properties as described above.
[0026] Here, the fibrous carbon nanostructure is not particularly limited and may include, for example, cylindrical carbon nanostructures such as CNTs, or non-cylindrical carbon nanostructures such as carbon nanostructures formed by a six-membered carbon ring network in a flattened shape. Meanwhile, the fibrous carbon nanostructure of the present invention may include only one of the above-described carbon nanostructures, or may include two or more types.
[0027] Furthermore, it is preferable that the fibrous carbon nanostructures include CNTs. This is because CNTs can exhibit excellent properties (e.g., conductivity, thermal conductivity, and strength) when their dispersibility is enhanced by surface modification treatment. Meanwhile, the fibrous carbon nanostructures containing CNTs may consist solely of CNTs, or they may be a mixture of CNTs and fibrous carbon nanostructures other than CNTs.
[0028] As for the CNT, single-layer carbon nanotubes and / or multilayer carbon nanotubes can be used, without being particularly limited. In addition, the CNT is preferably a carbon nanotube with a single to five layers, and a single-layer carbon nanotube is more preferable. This is because the fewer the number of layers of the CNT, the more excellent properties can be exhibited when dispersibility is increased by surface modification treatment.
[0029] Here, the fibrous carbon nanostructure of the present invention has a localized electron quantity obtained by electron spin resonance measurement at a temperature of 10K, which is 1.0 × 10⁻⁶ 17 It needs to be at least pieces / g, and 3.0 × 10 17 It is desirable that it be at least pieces / g, and 5.0 × 10 17 It is more preferable that it be at least pieces / g, and 1.0 × 10 18 It is more desirable that it be at least pieces / g, and 5.6 × 10 18 It is even more preferable that it be at least pieces / g, and 1.0 × 10 19 It is preferable that it be less than pieces / g, and 8.0 × 10 18It is more preferable that the number of localized electrons obtained by measuring electron spin resonance at a temperature of 10K is greater than or equal to the lower limit above, thereby sufficiently increasing the dispersibility of the fibrous carbon nanostructure after surface modification treatment. On the other hand, since the number of localized electrons obtained by measuring electron spin resonance at a temperature of 10K is less than or equal to the upper limit above, when surface modification treatment is performed on the fibrous carbon nanostructure, the loss of the fibrous carbon nanostructure after surface modification treatment is suppressed, and the surface-modified fibrous carbon nanostructure can be obtained efficiently.
[0030] Meanwhile, the amount of localized electrons obtained by measuring electron spin resonance of fibrous carbon nanostructures at a temperature of 10K can be adjusted by the thickness of the iron thin film (catalyst layer) in the catalyst substrate used in the method of manufacturing fibrous carbon nanostructures.
[0031] The average diameter of the fibrous carbon nanostructure is preferably 1 nm or more and preferably 60 nm or less. Additionally, the average diameter of the fibrous carbon nanostructure may be 2 nm or more, 3 nm or more, 30 nm or less, 10 nm or less, or 5 nm or less. A fibrous carbon nanostructure with an average diameter within the above-mentioned range can exhibit particularly excellent properties when its dispersibility is enhanced by surface modification treatment.
[0032] Meanwhile, the “average diameter of fibrous carbon nanostructures” can be obtained by measuring the diameter (outer diameter) of, for example, 20 fibrous carbon nanostructures in a transmission electron microscope (TEM) image and calculating the number average value.
[0033] In addition, as for the fibrous carbon nanostructure, it is preferable to use a fibrous carbon nanostructure in which the ratio (3σ / Av) of the standard deviation of the diameter (σ: sample standard deviation) multiplied by 3 to the average diameter (Av) is greater than 0.20 and less than 0.80, it is more preferable to use a fibrous carbon nanostructure in which 3σ / Av is greater than 0.25, and even more preferable to use a fibrous carbon nanostructure in which 3σ / Av is greater than 0.50. A fibrous carbon nanostructure in which 3σ / Av is greater than 0.20 and less than 0.80 can exhibit particularly excellent properties when dispersibility is increased by surface modification treatment.
[0034] Meanwhile, the average diameter (Av) and standard deviation (σ) of the fibrous carbon nanostructures may be adjusted by changing the manufacturing method or manufacturing conditions of the fibrous carbon nanostructures, or by combining multiple types of fibrous carbon nanostructures obtained by different manufacturing methods.
[0035] In addition, the fibrous carbon nanostructures preferably have an average length of 10 μm or more, more preferably 50 μm or more, even more preferably 80 μm or more, preferably 600 μm or less, even more preferably 550 μm or less, and even more preferably 500 μm or less. Fibrous carbon nanostructures having an average length within the above-mentioned predetermined range can exhibit particularly excellent properties when their dispersibility is enhanced by surface modification treatment.
[0036] Meanwhile, in the present invention, the "average length of the fibrous carbon nanostructure" can be obtained by measuring the length of, for example, 20 fibrous carbon nanostructures in a scanning electron microscope (SEM) image and calculating the number average value.
[0037] Here, the aspect ratio of the fibrous carbon nanostructure is typically greater than 10. Meanwhile, the aspect ratio of the fibrous carbon nanostructure can be obtained by measuring the diameter and length of 20 randomly selected fibrous carbon nanostructures using a scanning electron microscope or a transmission electron microscope, and calculating the average value of the ratio of diameter to length (length / diameter).
[0038] In addition, the BET specific surface area of the fibrous carbon nanostructure is 600 m² 2 It is desirable that it be greater than / g, and 800 m 2 It is more desirable to have / g or more, and 2000 m 2 It is desirable that it be / g or less, and 1800 m 2 It is more desirable that it be / g or less, and 1600 m 2 It is more desirable that it be / g or less, and 1100 m 2 / g Lee Hana, 1000 m 2 / g or less is acceptable. BET specific surface area is 600 m² 2 Fibrous carbon nanostructures with a specific surface area of 2000 m² or more can exhibit particularly excellent properties when their dispersibility is enhanced through surface modification treatment. In addition, the BET specific surface area is 2000 m² 2 Fibrous carbon nanostructures with a g or less can exhibit even better dispersibility after surface modification treatment.
[0039] In addition, it is preferable that the fibrous carbon nanostructure exhibits an upwardly convex shape in the t-plot obtained from the adsorption isotherm. Fibrous carbon nanostructures exhibiting an upwardly convex shape in the t-plot can exhibit particularly excellent properties when dispersibility is enhanced by surface modification treatment. Furthermore, it is more preferable that the fibrous carbon nanostructure does not undergo an opening treatment and exhibits an upwardly convex shape in the t-plot.
[0040] Meanwhile, the "t-plot" can be obtained by converting the relative pressure into the average thickness t (nm) of the nitrogen gas adsorption layer in the adsorption isotherm of a fibrous carbon nanostructure measured by the nitrogen gas adsorption method. That is, the t-plot of the fibrous carbon nanostructure is obtained by determining the average thickness t of the nitrogen gas adsorption layer corresponding to the relative pressure from a known standard isotherm plotting the average thickness t of the nitrogen gas adsorption layer against the relative pressure P / P0, and then performing the above conversion (t-plot method by de Boer et al.).
[0041] Here, in a material having pores on its surface, the growth of the nitrogen gas adsorption layer is classified into the following processes (1) to (3). And, a change in the slope of the t-plot occurs through the following processes (1) to (3).
[0042] (1) Process of forming a monomolecular adsorption layer of nitrogen molecules on the entire surface
[0043] (2) Formation of a multimolecular adsorption layer and the resulting capillary condensation filling process within the pores
[0044] (3) Process of forming a multimolecular adsorption layer on an apparent nonporous surface in which pores are filled with nitrogen
[0045] In addition, the t-plot, which exhibits an upwardly convex shape, is located on a straight line passing through the origin in the region where the average thickness t of the nitrogen gas adsorption layer is small, whereas as t increases, the plot is positioned downward from that straight line. A fibrous carbon nanostructure having such a t-plot shape indicates that the ratio of the internal specific surface area to the total specific surface area of the fibrous carbon nanostructure is large, and that a number of openings are formed in the carbon nanostructures constituting the fibrous carbon nanostructure.
[0046] Meanwhile, the inflection point of the t-plot of the fibrous carbon nanostructure is preferably in a range satisfying 0.2 ≤ t(nm) ≤ 1.5, more preferably in a range of 0.45 ≤ t(nm) ≤ 1.5, and even more preferably in a range of 0.55 ≤ t(nm) ≤ 1.0. A fibrous carbon nanostructure having an inflection point of the t-plot within the above-mentioned predetermined range can exhibit particularly excellent properties when dispersibility is enhanced by surface modification treatment.
[0047] Here, the “location of the bending point” is the intersection point of the approximate line A of the process of (1) described above and the approximate line B of the process of (3) described above.
[0048] In addition, the fibrous carbon nanostructure preferably has a ratio (S2 / S1) of the internal specific surface area S2 to the total specific surface area S1 obtained from a t-plot of 0.05 or higher, more preferably 0.07 or higher, even more preferably 0.10 or higher, and preferably 0.30 or lower. A fibrous carbon nanostructure in which the value of S2 / S1 is within the above predetermined range can exhibit particularly excellent properties when dispersibility is increased by surface modification treatment.
[0049] Here, the total specific surface area S1 and the internal specific surface area S2 of the fibrous carbon nanostructure can be obtained from the t-plot. Specifically, first, the total specific surface area S1 can be obtained from the slope of the approximate straight line of process (1), and the external specific surface area S3 can be obtained from the slope of the approximate straight line of process (3). Then, the internal specific surface area S2 can be calculated by subtracting the external specific surface area S3 from the total specific surface area S1.
[0050] In addition, the total specific surface area S1 and internal specific surface area S2 based on the measurement of the adsorption isotherm of the fibrous carbon nanostructure, the creation of a t-plot, and the interpretation of the t-plot can be performed, for example, using a commercially available measuring device, “BELSORP (registered trademark)-mini” (manufactured by Nippon Bell Co., Ltd.).
[0051] In addition, it is desirable for a fibrous carbon nanostructure containing CNTs suitable as a fibrous carbon nanostructure to have a Radial Breathing Mode (RBM) peak when evaluated using Raman spectroscopy. On the other hand, in the Raman spectrum of a fibrous carbon nanostructure composed solely of three or more layers of multilayer carbon nanotubes, an RBM does not exist.
[0052] In addition, it is preferable that the fibrous carbon nanostructure has a ratio of the G band peak intensity to the D band peak intensity in a Raman spectrum (G / D ratio) of 0.5 or more and 5.0 or less. In addition, the G / D ratio may be 1.5 or more, 2.0 or more, 2.5 or more, or 3.0 or more, and may also be 4.5 or less, 4.0 or less, or 3.4 or less. A fibrous carbon nanostructure with a G / D ratio of 0.5 or more and 5.0 or less can exhibit particularly excellent properties when dispersibility is increased by surface modification treatment.
[0053] And, the carbon purity of the fibrous carbon nanostructure is preferably 98 mass% or more, more preferably 99 mass% or more, and even more preferably 99.9 mass% or more.
[0054] Meanwhile, "carbon purity" can be obtained using the method described in the embodiments of this specification.
[0055] (Method for manufacturing fibrous carbon nanostructures)
[0056] The fibrous carbon nanostructure of the present invention described above can be efficiently manufactured by a method (e.g., see International Publication No. 2006 / 011655) in which, when synthesizing a fibrous carbon nanostructure by a CVD method by supplying a raw material compound and a carrier gas onto a substrate (catalyst substrate) having a catalyst layer on its surface, a small amount of oxidizing agent (catalyst activation material) is present in the system to dramatically improve the catalytic activity of the catalyst layer, wherein the formation of the catalyst layer on the substrate surface is performed by a wet process, and a raw material gas containing ethylene as a raw material compound (e.g., a gas containing more than 10 volume% of ethylene) is used.
[0057] Here, prior to the synthesis process in which a fibrous carbon nanostructure is synthesized by the CVD method by supplying a raw material compound and a carrier gas onto a catalyst substrate, a formation process may be optionally carried out in which the surrounding environment of the catalyst layer (e.g., a range where the distance from the catalyst layer is 5 cm or less) is made into a reducing gas environment, and at the same time, the catalyst layer and / or the reducing gas are heated. By carrying out the formation process, at least one effect among the reduction of the catalyst in the catalyst layer, the promotion of the micronization of the catalyst (making it into a state suitable for the growth of carbon structures), and the enhancement of the catalyst's activity is obtained.
[0058] In addition, after the above synthesis process, a cooling process may be optionally carried out to cool the synthesized fibrous carbon nanostructures and catalyst layer under an inert gas. By carrying out the cooling process, oxidation of the catalyst in the fibrous carbon nanostructures or catalyst layer can be prevented.
[0059] In addition, the formation process and cooling process may be carried out in accordance with, for example, the description in International Publication No. 2014 / 208097 or Japanese Patent Publication No. 2011-219316.
[0060] The catalyst substrate used in the method for manufacturing the fibrous carbon nanostructure described above has, for example, a catalyst layer and a catalyst supporting layer supporting the catalyst layer on the substrate. Furthermore, the catalyst layer is preferably an iron thin film, and the catalyst supporting layer is preferably an aluminum thin film. Here, "iron thin film" refers to a thin film containing metallic iron and / or an iron compound, and "aluminum thin film" refers to a thin film containing metallic aluminum and / or an aluminum compound.
[0061] In addition, in the manufacture of a catalyst substrate having the above catalyst layer, the formation of the catalyst layer on the substrate surface by a wet process can be performed, for example, by applying a coating solution A containing an aluminum compound onto the substrate, drying the coating film of coating solution A to form an aluminum thin film (catalyst supporting layer) on the substrate, and also by applying a coating solution B containing an iron compound onto the aluminum thin film, drying the coating film of coating solution B to form an iron thin film (catalyst layer) on the aluminum thin film.
[0062] Here, as a substrate, for example, a substrate made of metals such as iron, nickel, chromium, molybdenum, tungsten, titanium, aluminum, manganese, cobalt, copper, silver, gold, platinum, niobium, tantalum, lead, zinc, gallium, indium, germanium, and antimony, a substrate made of alloys or oxides of these metals, a substrate made of non-metals such as silicon, quartz, glass, mica, graphite, and diamond, or a substrate made of ceramics may be used.
[0063] In addition, as coating solution A, an aluminum compound, such as an organic aluminum compound and / or an aluminum salt capable of forming an alumina thin film as an aluminum thin film, may be used by dissolving or dispersing it in an organic solvent. Meanwhile, the concentration of the aluminum compound in coating solution A can be appropriately adjusted within the range in which the desired effect of the present invention is obtained.
[0064] Here, examples of organic aluminum compounds capable of forming an alumina thin film include aluminum alkoxides such as aluminum trimethoxide, aluminum triethoxide, aluminum tri-n-propoxide, aluminum tri-i-propoxide, aluminum tri-n-butoxide, aluminum tri-sec-butoxide, and aluminum tri-tert-butoxide. Other examples of organic aluminum compounds capable of forming an alumina thin film include aluminum complexes such as tris(acetylacetonato)aluminum(III). Additionally, examples of aluminum salts capable of forming an alumina thin film include aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum bromide, aluminum iodide, aluminum lactate, basic aluminum chloride, basic aluminum nitrate, etc.
[0065] Meanwhile, these aluminum compounds may be used as a single type or as a mixture of multiple types.
[0066] Meanwhile, organic solvents such as alcohols, glycols, ketones, ethers, esters, and hydrocarbons may be used as organic solvents. Meanwhile, these organic solvents may be used as a single type or as a mixture of multiple types.
[0067] In addition, as coating solution B, an iron compound, such as an organic iron compound and / or iron salt capable of forming an iron thin film, may be used by dissolving or dispersing it in an organic solvent. Meanwhile, the concentration of the iron compound in coating solution B can be appropriately adjusted within a range in which the desired effect of the present invention is obtained.
[0068] Here, organic iron compounds capable of forming an iron thin film include, for example, iron pentacarbonyl, ferrocene, acetylacetone iron (II), acetylacetone iron (III), trifluoroacetylacetone iron (II), and trifluoroacetylacetone iron (III). In addition, iron salts capable of forming an iron thin film include, for example, inorganic iron acids such as iron sulfate, iron nitrate, iron phosphate, iron chloride, and iron bromide, and organic iron acids such as iron acetate, iron oxalate, iron citrate, and iron lactate. Meanwhile, these iron compounds may be used as a single type or as a mixture of multiple types.
[0069] Meanwhile, the organic solvent included in coating solution B is not particularly limited, and, for example, the above-described organic solvent that can be used in coating solution A may be used.
[0070] In addition, the application and drying of the aforementioned coating solution A and coating solution B can be carried out using known methods.
[0071] For example, the application of coating solution A onto a substrate can be performed by the dip method. Specifically, this can be done by immersing the substrate in coating solution A, holding it therein, and then pulling it up. Here, conditions such as the time for holding the substrate in coating solution A and the pulling speed when pulling the substrate out of coating solution A can be appropriately set within the range where the desired effect of the present invention is obtained. Meanwhile, in the operation of immersing, holding, and pulling up the substrate in coating solution A in the dip method, the angle formed between the surface direction of the liquid surface of coating solution A and the surface direction of the substrate is not particularly limited and can be, for example, 90° (right angle).
[0072] In addition, conditions such as temperature and drying time when drying the coating film of coating liquid A formed on the substrate can also be appropriately set within the range where the desired effect of the present invention is obtained.
[0073] In addition, the thickness of the aluminum thin film formed on the substrate can be, for example, 10 nm or more and 100 nm or less.
[0074] Meanwhile, the thickness of the aluminum thin film can be adjusted by the lifting speed when lifting the substrate from the coating solution A.
[0075] In addition, for example, the application of coating solution B to an aluminum thin film formed on a substrate can be performed by the dip method. Specifically, this can be done by immersing the substrate on which the aluminum thin film is formed in coating solution B, holding it, and then pulling it up. Meanwhile, in the operation of immersing, holding, and pulling up the substrate in coating solution B in the dip method, the angle formed between the surface direction of the liquid surface of coating solution B and the surface direction of the substrate is not particularly limited and can be, for example, 90° (right angle).
[0076] Here, the time for maintaining the substrate on which the aluminum thin film is formed in the coating solution B can be, for example, from 5 seconds to 60 seconds.
[0077] In addition, when pulling up the substrate on which the aluminum thin film is formed from the coating solution B, the pulling speed is preferably 1 mm / sec or more, more preferably 2 mm / sec or more, even more preferably 3 mm / sec or more, preferably 18 mm / sec or less, more preferably 12 mm / sec or less, and even more preferably 8 mm / sec or less. If the pulling speed from the coating solution B is above the lower limit, the thickness of the iron thin film formed can be appropriately increased, and thus the predetermined amount of localized electrons in the fibrous carbon nanostructure produced can be appropriately reduced. On the other hand, if the pulling speed from the coating solution B is below the upper limit, the thickness of the iron thin film formed can be appropriately reduced, and thus the predetermined amount of localized electrons in the fibrous carbon nanostructure produced can be appropriately increased. Therefore, if the lifting speed when lifting the substrate on which the aluminum thin film is formed from the coating solution B is set within the above-mentioned predetermined range, the iron thin film formed can be made to have an appropriate film thickness, and thus the localized electron quantity of the manufactured fibrous carbon nanostructure can be easily made to fall within the above-mentioned predetermined range.
[0078] Meanwhile, conditions such as temperature and drying time when drying the coating film of coating solution B formed on the aluminum thin film can be appropriately set within the range in which the desired effect of the present invention is obtained.
[0079] In addition, the thickness of the iron thin film formed on the aluminum thin film is preferably 0.5 nm or more, more preferably 1 nm or more, even more preferably 2 nm or more, preferably 4.5 nm or less, even more preferably 4 nm or less, and even more preferably 3.5 nm or less. If the thickness of the iron thin film is greater than or equal to the lower limit above, the predetermined amount of localized electrons in the manufactured fibrous carbon nanostructure can be appropriately reduced. On the other hand, if the thickness of the iron thin film is less than or equal to the upper limit above, the predetermined amount of localized electrons in the manufactured fibrous carbon nanostructure can be appropriately increased. Therefore, if the thickness of the iron thin film is within the predetermined range above, the predetermined amount of localized electrons in the manufactured fibrous carbon nanostructure can be easily made to fall within the aforementioned predetermined range.
[0080] Meanwhile, the film thickness of the thin film can be adjusted by the pulling speed when pulling up the substrate on which the aluminum thin film is formed from the coating solution B.
[0081] (Method for manufacturing surface-modified fibrous carbon nanostructures)
[0082] The method for manufacturing a surface-modified fibrous carbon nanostructure according to the present invention is characterized by including a process (surface modification process) for obtaining a surface-modified fibrous carbon nanostructure by performing a surface modification treatment on the fibrous carbon nanostructure of the present invention described above. According to the method for manufacturing a surface-modified fibrous carbon nanostructure according to the present invention, a surface-modified fibrous carbon nanostructure with excellent dispersibility can be manufactured.
[0083] Meanwhile, the method for manufacturing a surface-modified fibrous carbon nanostructure according to the present invention may optionally include additional processes other than the surface modification treatment process.
[0084] Surface Modification Process
[0085] In the surface modification process, a surface modification treatment is performed on a fibrous carbon nanostructure to obtain a surface-modified fibrous carbon nanostructure.
[0086] Here, the surface modification treatment is not particularly limited, and, for example, wet treatment and dry treatment can be used.
[0087] Wet treatment can be performed using surface modification agents such as, for example, nitric acid, sulfuric acid, a mixture of nitric acid and sulfuric acid, and hydrogen peroxide. Additionally, dry treatment can be performed using surface modification agents such as, for example, oxygen, ozone, and fluorine gas.
[0088] Among these, from the perspective of obtaining surface-modified fibrous carbon nanostructures with even better dispersibility, it is preferable that the surface modification treatment be a wet oxidation treatment using nitric acid, sulfuric acid, or a mixture of nitric acid and sulfuric acid.
[0089] Meanwhile, the conditions for surface modification treatment can be set according to the type of surface modification agent used and the desired properties of the surface-modified fibrous carbon nanostructure.
[0090] Surface-modified fibrous carbon nanostructures
[0091] The surface-modified fibrous carbon nanostructure obtained by performing a surface modification treatment on the fibrous carbon nanostructure of the present invention can be well dispersed in a solvent, for example, water, without using a dispersant. Furthermore, the dispersion of the obtained surface-modified fibrous carbon nanostructure can be used to manufacture various molded articles (for example, films such as antistatic films or conductive films).
[0092] Here, in the dispersion of the surface-modified fibrous carbon nanostructure, since the surface-modified fibrous carbon nanostructure is well dispersed in the solvent, the amount of agglomeration can be reduced in the molded article manufactured using said dispersion. Therefore, the molded article made of the manufactured surface-modified fibrous carbon nanostructure exhibits excellent properties such as conductivity, thermal conductivity, and strength. In other words, the surface-modified fibrous carbon nanostructure can be said to have excellent properties as described above.
[0093] Examples
[0094] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. Meanwhile, in the following description, "%" indicating amount is based on mass unless otherwise specified.
[0095] In the examples and comparative examples, the G / D ratio, average diameter, BET specific surface area, t-plot, total specific surface area, internal specific surface area, carbon purity, and localized electron quantity of the fibrous carbon nanostructure containing CNT, and the dispersibility after surface modification treatment were each measured or evaluated by the following methods.
[0096] <G / D비>
[0097] Measurements were taken of fibrous carbon nanostructures near the center of the substrate using a micro-laser Raman system (manufactured by Thermo Fisher Scientific, Inc., NicoletAlmega XR).
[0098] <Average Diameter>
[0099] The diameter (outer diameter) of 20 randomly selected fibrous carbon nanostructures was measured from images obtained using a transmission electron microscope, and the average value was calculated.
[0100] <BET 비표면적, t-플롯, 전체 비표면적 및 내부 비표면적>
[0101] The specific surface area was measured using a BET specific surface area measuring device (manufactured by Nippon Bell Co., Ltd., BELSORP (registered trademark)-mini).
[0102] Carbon Purity
[0103] Using a thermogravimetric analyzer (TG), the carbon purity (= (mass reduced by combustion until reaching 800°C / initial mass) × 100 (%)) was determined from the mass reduction when the fibrous carbon nanostructure was heated to 800°C in air.
[0104] International Electronic Amount
[0105] Using an electron spin resonance device (BRUKER Elexsys E580), copper sulfate pentahydrate was used as a standard sample, and the localized electron quantity of fibrous carbon nanostructures was quantified from the ratio of signal intensity at a temperature of 10K to the sample weight.
[0106] <Dispersibility after surface modification treatment>
[0107] <<Evaluation of Dispersion>>
[0108] For a dispersion of surface-modified fibrous carbon nanostructures, the centrifugation was performed using a centrifuge (manufactured by Beckmann Coulter, product name "OPTIMA XL100K") at 20,000 G for 40 minutes, and the cycle of recovering the supernatant was repeated three times to obtain 20 mL of the dispersion of surface-modified fibrous carbon nanostructures after centrifugation. The presence or absence of agglomerations in this dispersion was checked by visual inspection. If no agglomerations are observed by visual inspection, it indicates that the fibrous carbon nanostructures have excellent dispersibility after surface modification treatment.
[0109] In addition, regarding the particles present in the dispersion after the above centrifugation treatment, the particle size was measured using a Dynamic Light Scattering (DLS) particle size analyzer (manufactured by Malvern, product name "Zetasizer Nano ZS"), and the dispersibility of the surface-modified fibrous carbon nanostructures was evaluated. Meanwhile, a smaller particle size indicates that the fibrous carbon nanostructures are well surface-modified, and that the dispersibility after the surface modification treatment is excellent.
[0110] <<Evaluation of Molded Products (Films)>>
[0111] In addition, a dispersion of surface-modified fibrous carbon nanostructures was applied to a glass substrate using Bar Coater #2, and then dried at 130°C for 10 minutes to form a film of surface-modified fibrous carbon nanostructures on the glass substrate. The obtained film was then observed under an optical microscope (magnification 100x), and the dispersibility of the surface-modified fibrous carbon nanostructures was evaluated by confirming the presence or absence of aggregates (diameter 30 μm or more) of the surface-modified fibrous carbon nanostructures visible in the field of view of the microscope. If no aggregates of the surface-modified fibrous carbon nanostructures are observed in the field of view of the microscope, it indicates that the fibrous carbon nanostructures have been surface-modified well and that the dispersibility after the surface modification treatment is excellent.
[0112] <<Overall Evaluation>>
[0113] When there are no aggregates in the dispersion of surface-modified fibrous carbon nanostructures, and the particle size measured using a dynamic light scattering (DLS) particle size distribution meter is 180 nm or less, and there are no aggregates in the film, it is rated as “excellent,” and in all other cases, it is rated as “unacceptable.”
[0114] (Example 1)
[0115] <Manufacture of catalyst substrate>
[0116] Coating solution A was prepared by dissolving aluminum tri-sec-butoxide in 2-propanol. Additionally, coating solution B was prepared by dissolving iron acetate in 2-propanol.
[0117] The above-described coating solution A was applied to the surface of a stainless steel substrate as a flat substrate to form an alumina thin film (catalyst supporting layer) with a film thickness of 40 nm. Subsequently, the above-described coating solution B was applied onto the alumina thin film formed on the substrate by a dip method at a pulling speed of 5 mm / sec to obtain a substrate (catalyst substrate) having an iron thin film with a film thickness of 2 nm as a catalyst layer.
[0118] Synthesis of Fibrous Carbon Nanostructures
[0119] An oriented aggregate of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs) was synthesized by sequentially performing a formation process (reduction process), a synthesis process, and a cooling process on the aforementioned catalyst substrate. Meanwhile, in the formation process, hydrogen gas was supplied to the catalyst substrate to perform a reduction treatment. In addition, in the synthesis process, a source gas (including ethylene gas, nitrogen gas as a carrier gas, and water as an activator) was supplied to the catalyst substrate.
[0120] The obtained fibrous carbon nanostructures containing CNTs had a G / D ratio of 3.8, an average diameter of 4 nm, and a BET specific surface area of 1446 cm². 2 / g, carbon purity of 99.9%, and 100 ~ 300 cm² characteristic of single-layer carbon nanotubes in Raman spectrophotometry measurements -1 A peak of the Radial Breathing Mode (RBM) was observed in the low wavenumber region. Additionally, the t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was curved in an upwardly convex shape. The location of the inflection point was t = 0.7 nm, and the total specific surface area S1 was 970 m². 2 / g, and the internal specific surface area S2 is 170 m2 / g, and S2 / S1 was 0.18. In addition, the localized electron quantity of the obtained fibrous carbon nanostructure containing CNTs at a temperature of 10K was 5.6 × 10⁻⁶. 18 It was g.
[0121] <Preparation of Dispersion of Surface-Modified Fibrous Carbon Nanostructures>
[0122] In a 300 mL flask equipped with a cooling tube and a stirring blade, 0.80 g of the fibrous carbon nanostructure containing the CNT obtained above, 54.8 g of ion-exchanged water, and 83 mL of a mixed acid solution containing sulfuric acid (manufactured by Wako Junyakusha, concentration 96-98%) and nitric acid (manufactured by Wako Junyakusha, concentration 69-70%) in a ratio of 1:3 (volume ratio) were added, and then the mixture was heated at a temperature of 110°C for 8 hours while stirring to perform a mixed acid treatment as a wet oxidation treatment.
[0123] 3.0 g of the liquid mixture of fibrous carbon nanostructures / mixed acid obtained after mixed acid treatment was weighed into a 50 mL sample bottle, and 27.0 g of deionized water was added to dilute it. After removing the supernatant, deionized water was added to make the liquid volume 30 mL. After adding 0.1% ammonia water to adjust the pH to 7.0, ultrasonic irradiation was performed for 50 minutes at a frequency of 42 Hz using an ultrasonic irradiation device (manufactured by Branson, product name "BRANSON5510") to obtain a dispersion of surface-modified fibrous carbon nanostructures.
[0124] Using the obtained dispersion of surface-modified fibrous carbon nanostructures, the dispersibility of the fibrous carbon nanostructures after surface modification treatment was evaluated. The results are shown in Table 1.
[0125] (Example 2)
[0126] The synthesis of fibrous carbon nanostructures and the preparation of a dispersion of surface-modified fibrous carbon nanostructures were carried out under the same conditions as in Example 1, except that the thickness of the iron thin film formed was changed from 2 nm to 3 nm by changing the lifting speed when applying coating solution B to the alumina thin film formed on the substrate from 5 mm / sec to 10 mm / sec. Then, various measurements and evaluations were performed in the same manner as in Example 1.
[0127] The obtained fibrous carbon nanostructures containing CNTs had a G / D ratio of 2.9, an average diameter of 4 nm, and a BET specific surface area of 1191 cm². 2 / g, carbon purity of 99.9%, and 100 ~ 300 cm² characteristic of single-layer carbon nanotubes in Raman spectrophotometry measurements -1 A peak of the Radial Breathing Mode (RBM) was observed in the low wavenumber region. Additionally, the t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was curved in an upwardly convex shape. The location of the inflection point was t = 0.7 nm, and the total specific surface area S1 was 840 m². 2 / g, and the internal specific surface area S2 is 70 m 2 / g, and S2 / S1 was 0.08. In addition, the localized electron quantity of the obtained fibrous carbon nanostructure containing CNTs at a temperature of 10K was 9.9 × 10⁻⁶. 17 It was g.
[0128] In addition, the results of evaluating the dispersibility of the fibrous carbon nanostructures after surface modification treatment using the obtained dispersion of the surface-modified fibrous carbon nanostructures are shown in Table 1.
[0129] (Example 3)
[0130] The synthesis of fibrous carbon nanostructures and the preparation of a dispersion of surface-modified fibrous carbon nanostructures were carried out under the same conditions as in Example 1, except that the thickness of the iron thin film formed was changed from 2 nm to 4 nm by changing the lifting speed when applying coating solution B to the alumina thin film formed on the substrate from 5 mm / sec to 15 mm / sec. Then, various measurements and evaluations were performed in the same manner as in Example 1.
[0131] The obtained fibrous carbon nanostructures containing CNTs had a G / D ratio of 1.9, an average diameter of 4 nm, and a BET specific surface area of 1104 cm². 2 / g, carbon purity of 99.9%, and 100 ~ 300 cm² characteristic of single-layer carbon nanotubes in Raman spectrophotometry measurements -1 A peak of the Radial Breathing Mode (RBM) was observed in the low wavenumber region. Additionally, the t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was curved in an upwardly convex shape. The position of the inflection point was t = 0.7 nm, and the total specific surface area S1 was 800 m² 2 / g, and the internal specific surface area S2 is 40 m 2 / g, and S2 / S1 was 0.05. In addition, the localized electron quantity of the obtained fibrous carbon nanostructure containing CNTs at a temperature of 10K was 4.9 × 10⁻⁶. 17 It was g.
[0132] In addition, the results of evaluating the dispersibility of the fibrous carbon nanostructures after surface modification treatment using the obtained dispersion of the surface-modified fibrous carbon nanostructures are shown in Table 1.
[0133] (Comparative Example 1)
[0134] The synthesis of fibrous carbon nanostructures and the preparation of a dispersion of surface-modified fibrous carbon nanostructures were carried out under the same conditions as in Example 1, except that the thickness of the iron thin film formed was changed from 2 nm to 5 nm by changing the lifting speed when applying coating solution B to the alumina thin film formed on the substrate from 5 mm / sec to 20 mm / sec. Then, various measurements and evaluations were performed in the same manner as in Example 1.
[0135] The obtained fibrous carbon nanostructures containing CNTs had a G / D ratio of 3.5, an average diameter of 4 nm, and a BET specific surface area of 1113 cm². 2 / g, carbon purity of 99.9%, and 100 ~ 300 cm² characteristic of single-layer carbon nanotubes in Raman spectrophotometry measurements -1 A peak of the Radial Breathing Mode (RBM) was observed in the low wavenumber region. Additionally, the t-plot of the fibrous carbon nanostructure obtained from the adsorption isotherm was curved in an upwardly convex shape. The location of the inflection point was t = 0.7 nm, and the total specific surface area S1 was 1120 m². 2 / g, and the internal specific surface area S2 is 120 m 2 / g, and S2 / S1 was 0.11. In addition, the localized electron quantity of the obtained fibrous carbon nanostructure containing CNTs at a temperature of 10K was 8.4 × 10⁻⁶. 16 It was g.
[0136] In addition, the results of evaluating the dispersibility of the fibrous carbon nanostructures after surface modification treatment using the obtained dispersion of the surface-modified fibrous carbon nanostructures are shown in Table 1.
[0137] (Comparative Example 2)
[0138] As an orientation assembly of fibrous carbon nanostructures (fibrous carbon nanostructures containing CNTs), a dispersion of surface-modified fibrous carbon nanostructures was prepared using "e-DIPS" manufactured by Meizo Nanocarbon Co., Ltd., which is a single-layer carbon nanotube, and the dispersibility after surface modification treatment was evaluated. The results are shown in Table 1.
[0139] Meanwhile, in the dispersion of the obtained surface-modified fibrous carbon nanostructures, the surface-modified fibrous carbon nanostructures formed extremely large aggregates, so the particle size could not be measured and a film could not be formed.
[0140] In addition, the "e-DIPS" manufactured by Meizo Nanocarbon Co., Ltd. used above has a BET specific surface area of 900 cm² 2 / g, and the localized electron quantity at a temperature of 10K is 4.0 × 10 16 It was less than 1 / g (below the lower detection limit).
[0141]
[0142] From Table 1, it can be seen that the fibrous carbon nanostructures of Examples 1 to 3, in which the amount of localized electrons obtained by electron spin resonance measurement at a temperature of 10K is greater than a predetermined value, have excellent dispersibility after surface modification treatment.
[0143] Meanwhile, it can be seen that the fibrous carbon nanostructures of Comparative Examples 1 and 2, in which the amount of localized electrons obtained by electron spin resonance measurement at a temperature of 10K is less than a predetermined value, have poor dispersibility after surface modification treatment.
[0144] Industrial applicability
[0145] According to the present invention, a fibrous carbon nanostructure with excellent dispersibility after surface modification treatment can be provided.
[0146] In addition, according to the present invention, a surface-modified fibrous carbon nanostructure with excellent dispersibility can be provided.
Claims
Claim 1 The localized electron quantity obtained from electron spin resonance measurements at a temperature of 10K is 1.0 × 10 17 A fibrous carbon nanostructure having a number of pieces / g or more, and a ratio of the G band peak intensity to the D band peak intensity in a Raman spectrum (G / D ratio) of 0.5 or more and 5.0 or less. Claim 2 In paragraph 1, the local electron quantity is 1.0 × 10 19 Fibrous carbon nanostructures with less than 1 / g. Claim 3 A fibrous carbon nanostructure according to claim 1, wherein the t-plot obtained from the adsorption isotherm exhibits an upwardly convex shape. Claim 4 A fibrous carbon nanostructure comprising carbon nanotubes in claim 1. Claim 5 In paragraph 4, the fibrous carbon nanostructure comprises carbon nanotubes including single-layer carbon nanotubes. Claim 6 A method for manufacturing a surface-modified fibrous carbon nanostructure, comprising a process of obtaining a surface-modified fibrous carbon nanostructure by performing a surface modification treatment on a fibrous carbon nanostructure described in any one of claims 1 to 5. Claim 7 A method for manufacturing a surface-modified fibrous carbon nanostructure according to claim 6, wherein the surface modification treatment is a wet oxidation treatment. Claim 8 delete
Citation Information
Patent Citations
Method for producing carbon fiber
JP2003013330A
Metal matrix composite and production method thereof
JP2016183395A
Fibrous carbon nanostructure dispersion and method for producing same, and fibrous carbon nanostructure
KR1020190127745A
Carbon nanotube film and method for producing same
WO2016103706A1
